Pelatihan Membaca Al Qur`an Untuk Meningkatkan Kepercayaan Diri Di MA Darul Ulum Palangka Raya - Said Sultan Abdillah; Noorazmah Hidayati; Mila Nur Aini (CV. ALIM'SPUBLISHING, 2025)
This training aims to improve fluency in reading the Al-Qur'an accompanied by students and lecturers through one of the Teaching Assistance KKN programs, namely training fluency in reading the Al-Qur'an at MA Darul Ulum Palangka Raya. The service process uses the Asset Based Community Development (ABCD) approach. Before the training was carried out, fluency in reading the Qur'an was still not fluent, this was seen based on the results of observations, namely when poets such as Habsyi appeared confident in singing poetry but when reading the Qur'an for the reading of the divine kalam the students did not have the courage so they gave it a try. go back to the teacher there who is more experienced. The results of training on students' fluency in reading the Al-Qur'an through joint Koran activities, which was carried out for 3 months using the ABCD approach, can be concluded that students' fluency in reading the Al-Qur'an increased with the training, which helped students overcome problems that makes you feel less confident, such as feeling that your recitation of Tajwid is not good enough or that you are less confident in your Koran songs, so this is where fluency training comes into play. Keywords: Reading the Koran, Fluency, Confidence